Effect of Ocimum gratissimum plant leaf extract concentration and annealing temperature on the structure and optical properties of synthesized zinc oxide nanoparticles - Mfon, Rebecca Emmanuel; Hall, Simon R; Sarua, Andrei (EDUCATUM Journal of Science, Mathematics and Technology, 2020)
Zinc oxide nanoparticles biosynthesized using two concentrations of Ocimum gratissimum (Og) plant leaf extracts were annealed at two different  temperatures. Their UV-Vis absorbance peaks  at 372 nm - 375 nm indicate a blue shift in excitonic absorption and  their  optical energy band gap values were in the range 3.22 eV – 3.31 eV.   SEM images show the nanoparticles to be polydispersed and of a wide range of sizes with smaller nanoparticles clustering around bigger micrometer- sized ones with sharp edges. An annealing temperature of 400  resulted in the sintering of the nanoparticles but nanoparticles annealed at 250   had porous surfaces suggesting a possible use in gas sensor applications. XRD patterns show that the ZnO nanoparticles have the hexagonal wurtzite structure and are of good crystalline structure.  Obtained crystallite sizes increased with annealing temperature and were in the range 14 nm to 29 nm.  FTIR spectra show phenols, amines and aldehydes as the available reducing agents involved in the nanoparticle synthesis. The photoluminescence (PL) spectra show two emission peaks: a UV emission peak at 369 -381 nm indicating that the zinc oxide nanoparticles exhibited band-edge photoluminescence and a green emission peak at 523 nm – 538 nm suggesting the presence of defects from singly ionized oxygen vacancies. The PL peak intensities were dependent on the annealing temperatures with the UV- emission peaks for higher annealing temperatures exhibiting a spectral shift towards lower wavelengths.  Plant leaf extracts concentration and the annealing temperatures used affect the structure and optical properties of the synthesized ZnO nanoparticles.